Multidrug-Resistant Lineage of Enterotoxigenic Escherichia coli ST182 With Serotype O169:H41 in Airline Waste - Jarocki, Veronica M.; Heß, Stefanie; Anantanawat, Kay; Berendonk, Thomas U.; Djordjevic, Steven P. (Frontiers in Microbiology, 2021)
Enterotoxigenic Escherichia coli (ETEC) is the primary etiologic agent of traveller’s diarrhea and a significant cause of diarrheal disease and death in developing countries. ETEC O169:H41 strains are known to cause both traveller’s diarrhea and foodborne outbreaks in developed countries and are cause for concern. Here, whole-genome sequencing (WGS) was used to assemble 46 O169:H41 (ST182) E. coli draft genomes derived from two airplane waste samples sourced from a German international airport. The ST182 genomes were compared with all 84 publicly available, geographically diverse ST182 genomes to construct a core genome-based phylogenetic tree. ST182 isolates were all phylogroup E, the majority serotype O169:H41 (n=121, 93%) and formed five major clades. The airport waste isolates differed by an average of 15 core SNPs (range 0-45) but their accessory genome content was diverse. While uncommon in other ST182 genomes, all airplane-derived ST182 isolates carried; i) extended-spectrum β-lactamase gene blaCTX-M-15 notably lacking the typical adjacent ISEcp1; ii) qnrS1 and the S83L mutation in gyrA, both conferring resistance to fluoroquinolones and iii) a class 1 integron structure (IS26-intI1Δ648-dfrA17-aadA5-qacEΔ1-sul1-ORF-srpC-padR-IS6100-mphR-mrx-mphA-IS26) identified previously in major extraintestinal pathogenic E. coli STs but not in ETEC. ST182 isolates carried ETEC-specific virulence factors STp + CS6. Adhesin/invasin tia was identified in 89% of aircraft ST182 isolates (vs 23%) and was located on a putative genomic island within a hotspot region for various insertions including PAII536 and plasmid-associated transposons. The most common plasmid replicons in this collection were IncFII (100%; F2:A-:B-) and IncB/O/K/Z (89%). Our data suggest that potentially through travel, E. coli ST182 isolates and are evolving a multidrug-resistant profile through the acquisition of class 1 integrons and different plasmids.